2009
DOI: 10.1167/iovs.09-3602
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Immune Modulator Programmed Cell Death-1 during Development and Apoptosis of Mouse Retinal Ganglion Cells

Abstract: PURPOSE Mammalian programmed cell death-1 (PD-1) is a membrane-associated receptor regulating the balance between T cell activation, tolerance and immunopathology, however its role in neurons has not yet been defined. We investigate the hypothesis that PD-1 signaling actively promotes retinal ganglion cell (RGC) death within the developing mouse retina. METHODS Mature retinal cell types expressing PD-1 were identified by immunofluorescence staining of vertical retina sections; developmental expression was lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 43 publications
3
30
0
Order By: Relevance
“…Concordant with its functions in the immune system, we further demonstrated that PD-1 and its partner(s) play an important role in RGC death during retinal development (Chen et al, 2009b; Sham et al, 2012). It is known that pathological RGC degeneration may share the same mechanisms as those in physiological RGC loss; therefore, we investigated whether PD-1 is involved in RGC apoptosis in pathological settings.…”
Section: Introductionsupporting
confidence: 59%
See 2 more Smart Citations
“…Concordant with its functions in the immune system, we further demonstrated that PD-1 and its partner(s) play an important role in RGC death during retinal development (Chen et al, 2009b; Sham et al, 2012). It is known that pathological RGC degeneration may share the same mechanisms as those in physiological RGC loss; therefore, we investigated whether PD-1 is involved in RGC apoptosis in pathological settings.…”
Section: Introductionsupporting
confidence: 59%
“…In the developing retina, PD-1 expression undergoes dynamic regulation and correlates with the time of active RGC culling (Chen et al, 2009b). The level of PD-1 expression decreases after the early postnatal stage, and remains low but measurable in the adult retina.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This result was unexpected, because several studies proposed that this pathway primarily affects generation of IFN-g-producing T H 1 cells (41)(42)(43)(44). Another aspect that argues against a general interference with T cell responses by B7-H1 is the selective promoting effect of B7-H1-Ig on murine TGF-bmediated inducible T reg (iT reg ) differentiation, in line with other studies (30,45,46). However, it has been reported that induction of iT reg generation and function by B7-H1 is mediated via PD-1 (30,46).…”
Section: Discussionmentioning
confidence: 62%
“…For each eye, at least 5 central retinal sections were analyzed at the level of the ON to the periphery and the results averaged, as previously described (14). In parallel, TUNEL-positive GCL nuclei were counted and expressed as a fraction of the total GCL nuclei (58,(73)(74)(75)(76). For in vitro experiments, RGCs were isolated, treated, and probed with an antibody to β3-tubulin and imaged as above.…”
Section: Author Contributionsmentioning
confidence: 99%